An improved spectral approach for solving the nonclassical neutral particle transport equation. (November 2022) - Moraes, L.R.C.; Patel, J.K.; Barros, R.C.; Vasques, R.
Highlights: An improved version of the Spectral Approach. Introduction of an arbitrary parameter α to the representation of the nonclassical angular flux as a truncated Laguerre series. The influence of the new parameter α on the solution for a specific case. Numerical results for analysis of the possible improvement of efficiency by using the modified spectral method. Abstract: An improved modification of the Spectral Approach (SA) used for approximating the nonclassical neutral particle transport equation is described in this work. The term "Spectral" is used to indicate that the nonclassical angular flux is approximated as an expansion in terms of spectral basis functions. In the SA the basis functions are the Laguerre polynomials. The main focus of the modified SA lies on a slight modification of the nonclassical angular flux representation as a truncated Laguerre series. This leads, in some cases, to a considerable decrease of the Laguerre truncation order required to generate accurate solutions, thus improving efficiency. Numerical results are given to illustrate this offered improvement.